2019
DOI: 10.1002/jbm.b.34406
|View full text |Cite
|
Sign up to set email alerts
|

Tethered‐liquid omniphobic surface coating reduces surface thrombogenicity, delays clot formation and decreases clot strength ex vivo

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
12
1
Order By: Relevance
“…[ 24 ] The mechanical strength of clots formed on TLP was found to be weaker compared to those found on untreated controls as determined by thromboelastography (TEG). [ 44 ] Therefore, we would expect HO PS as well as TP and TLP to produce sparsely packed fibrin clots with thicker fibers than hydrophilic materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 24 ] The mechanical strength of clots formed on TLP was found to be weaker compared to those found on untreated controls as determined by thromboelastography (TEG). [ 44 ] Therefore, we would expect HO PS as well as TP and TLP to produce sparsely packed fibrin clots with thicker fibers than hydrophilic materials.…”
Section: Resultsmentioning
confidence: 99%
“…[ 41 ] The authors of the latter study proposed that the depletion of lubricant over extended periods may have led to the reduction in the effectiveness of the coatings. [ 41 ] Despite studies of TLP prolonging the clotting time (CT) of blood plasma, [ 42 ] reducing thrombin generation, [ 43 ] fibrin polymerization rate, and clot strength, [ 44 ] in vitro, and positive short‐term in vivo studies, [ 34,40 ] the mechanisms underpinning the anti‐thrombogenic behavior of TLP surfaces have largely remained unexplored. [ 37 ] This knowledge may allow optimization of the coating to enhance performance and withstand longer term applications.…”
Section: Introductionmentioning
confidence: 99%
“…93,94 Roberts et al reported the use of TLP to reduce surface thrombogenicity during real-time clot formation using thromboelastography. 95 Optimization of the preparation of this omniphobic surface was also pursued. Badv et al reported that they used chemical vapor deposition (CVD) instead of commonly used liquid-phase deposition (LPD) of fluorine-based organosilanes, and the CVD method was more efficient and reproducible, resulting in less disruption of the outer polymeric layer of the catheters and produced increased activity of anti-thrombotic pathways.…”
Section: And Pf4mentioning
confidence: 99%
“…However, exposure of the lubricant layers to an air and water interface significantly increased the amount of lubricant removed from the surface, leading to disruption of the layer . This is due to these low surface energy liquids being inclined to form a wrapping layer over single water droplets in air and then cause the progressive loss of the impregnated low surface energy liquids through entrainment in the water droplets as they are shed from the surface. , Roberts et al reported the use of TLP to reduce surface thrombogenicity during real-time clot formation using thromboelastography . Optimization of the preparation of this omniphobic surface was also pursued.…”
Section: Coatings On Oxygenator Membranes Under Developmentmentioning
confidence: 99%
“…In this study, thromboelastography (TEG) was performed. TEG has been widely used in various applications, ranging from coagulation management in clinical testing to the evaluation of newly designed biomaterials [31][32][33]. In addition, TEG allows the localized measurement of whole blood coagulation on a material surface, including initiation of clot formation, rate of clot formation, and clot strength.…”
Section: Introductionmentioning
confidence: 99%